#TITLE_ALTERNATIVE# - AMANDA (NIM 13203039), DITA
The IEEE 802.16d standard is the latest Fixed Broadband Wireless Access (BWA) standard that being approved by IEEE. This standard operates in 2—11 GHz range and touted as an important step towards widespread adoption of BWA. BWA offers high speed voice, video, and data services. The biggest advantage BWA has over its competitor that is presently dominated by the cable and digital subscriber line (DSL) is its increased capacity and ease of deployment. In this Final Project report, the writer learns about channel modeling algorithm for IEEE 802.16d system, using SUI model. This model is being chosen because of its lack of complexity and its capability to represent almost all area that consist of rural, suburban, and urban area. The effects of system parameters, such as Doppler Spectrum, Fading Characteristics, Path Loss, and Delay Spread, are investigated using computer simulations. To perform this simulation, writer used two helpful software that is Matlab 7.0.4 and LabView 8.0. It is later turn out that channel performance can not be closer to AWGN performance without any channel estimation. Therefore, writer proposes 8 pilot tones and compares two insertion techniques; comb and block, to improve channel performance. The IEEE 802.16d performances successfully being improved with block insertion technique. The reason is because block estimator has the frequency resolution to accurately represent the channel, and gives more correct result. Using SUI model to predict channel condition and block estimator to improve channel performance may give brief description on the challenges faced and obstacles that have to be overcome before the deployment of IEEE 802.16d networks could be realized.